Hubungan Interaksi Sosial Dengan Kualitas Hidup Lansia Di Desa Ceurih Kecamatan Ulee Kareng Kota Banda Aceh - Muhammad Iqbal S; Azhar Mu'alim; Yadi Putra (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Introduction: The aging process causes the elderly to slowly withdraw from social, having a detrimental effect on their capacity to interact with others. Social interaction which is a crucial aspect of interpersonal interaction can improve elderly people's quality of life. lack it Social interaction makes elderly lonely and frequently affects the health and social roles in society to decline. This study's objective was to ascertain the relationship between social interaction and elderly quality of life. Methods: The research design It's a comparative descriptive with approach cross-sectional study. According to the total number of elderly people registered at the Posbindu Ceurih Village, the population in the study amounted to 45 respondents. Sampling with total sampling and the accidental sampling techniques. The research was conducted out by 18 to 30 December 2022. Methods of data collection with social interaction questionnaires and WHOQOL questionnaires to quality of life. Result: The research's result, the majority of elderly people's social interactions (29 respondents, or 64.4%) fell into unfavorable category, while (27 respondents, or 60%) reported that their quality of life was generally good. Conclusion: The research results of the correlation test indicate that there is a relationship between social interaction and the quality of life of the elderly (p value=0,000). Suggestions: It is desired that the Ulee Kareng Health Center and village cadres can add and include schedules for the daily activities of the elderly so that the elderly can often gather and interact with each other which is their daily routine